SYARIAT DALAM BALUTAN IBADAT DAN ADAT - Haedar Aly (IBDA` : Jurnal Kajian Islam dan Budaya, 2015)
This paper is discussed about syariat/Islamic law especially on the development of the contents. The main point of discussion refers to the position of tradition in ritual Islamic prayer. This paper is divided into two parts; the first one is analysed the meaning and development of ritual and tradition from theology and socio-anthrophology point of fiew. This part is very important to understand the position of ritual and tradition. The second part is discussed the relationship between ritual and traditionin Islamic law perspective. The existence of a religion is always presence a mediators which is acquired as the most authoritative on give meaning and state the religion rules which comes from God. The rules and meaning that they made is closely connected to their sociocultural life.